Reservoir-condition pore-scale imaging -contact angle, wettability, dynamics and trapping - Andrew,MG; Bijeljic,B; Blunt,MJ (2014)
Firstly capillary trapping is examined in a range of five different rock types, including both carbonates and sandstones. Rocks are imaged both after drainage and imbibition, and in all cases between 65-70% of the CO2 in place after drainage was trapped. Trapped cluster size distributions are compared to rock connectivity as determined using pore network modelling. Better connected pore-spaces tend to have more large clusters relative to small clusters, and visa-versa. This is important as small clusters are more difficult to remobilise by viscous and gravitational forces. They also present a relatively larger surface area for reaction and mineralization. Secondarily wettability is analysed by measuring contact angle manually. In order to do this the contact line was found in 3D and the data set resampled onto planes perpendicular to the contact line at a particular point. Contact angles ranging from 35-55o were found, indicating that the super-critical CO2-brine-carbonate system is weakly water wet. The range in contact angles is interpreted as the result of contact angle hysteresis associated with surface heterogeneity. Finally the first images of CO2 drainage at reservoir conditions are also presented, imaged at Diamond Light Source, represented an unprecented depth of information about pore-scale flow processes.